The challenges of rehabilitation after COVID-19 - Szymczyk, Ewelina; Wolska, Joanna; Wolski, Dariusz (Journal of Education, Health and Sport, 2021)
Due to the outbreak of the COVID-19 pandemic, social life and the clinical state of change of state. This disease is caused by the SARS-CoV-2 virus and is characterized by high infectivity and mortality. Due to the diversity of the tested tests, it will be difficult to obtain uniform characteristics, resulting in a uniform recovery plan for each patient. Rehabilitation, repair, execution, restoration to health, independence and reduction in value due to COVID-19.